Capital in the mirror : critical social theory and the aesthetic dimension - Krier, Dan, 1965-; Worrell, Mark P. (SUNY series in new political science, 2020)
"Aesthetic objects, crafted as poetic reflections of the contradictory worlds that they inhabit, are simultaneously theorized and theorizing. In Capital in the Mirror: Critical Social Theory and the Aesthetic Dimension, eminent critical theorists explore the aesthetic dimension for reflective visions of capital that are difficult to obtain through even the most rigorous statistical analyses. Chapters work together to analyze capitalism through the prism of acclaimed aesthetic products by Herman Melville, Thomas Mann, Charles Dickens, J.W. Goethe, Friedrich Hïlerlin, Walt Whitman, Berthold Brecht, and science fiction cinema. Famous narrative elements in these works, such as Ahab's pursuit of the white whale in Melville's Moby Dick; demonic production and perverse desire in Mann's Doctor Faustus, socially electrified bodies of Whitman's Leaves, dystopian projections of current sci-fi cinema, are theorized as stylistically-distorted reflections of social life within capital. The authors reveal theoretical powers latent within these condensed images that prefigure the dark dynamics of capitalism. The book is divided into two sections: one devoted to dark images of domination (Twilight) and a second devoted to prophetic images of transformation (Dawn), pointing the way toward emancipation, social regeneration, and human flourishing"--Provided by publisher